Net neutrality regulation: Much ado about nothing? - Ingo Vogelsang (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2019)
The economics literature on Net Neutrality (NN) has been largely critical of NN regulation on the basis of theoretical findings that NN violations can be both welfare improving and welfare deteriorating, depending on the circumstances of the case in question. Thus, an ex post competition policy approach would be preferable to a strict ex ante prohibition of NN violations. In contrast, the current paper argues that NN regulation is largely ineffective, in particular, when it comes to the prohibition of fast lanes and other quality of service (QoS) differentiations, and to a lesser extent, when it comes to the zero price rule. NN regulation is effective only in preventing the blocking of specific content and in preventing the favoring of ISP owned content and in preventing some price discriminations. These are also areas where NN regulations are more likely to be welfare-enhancing. Where they are ineffective, NN regulations are likely to create inefficiencies through the cost and allocative inefficiencies caused by NN bypass. The paper ends with a call for theoretical and empirical economic analyses of NN circumvention techniques.
Keywords: L50; L96; 330; net neutrality (NN); quality of service (QoS); price discrimination; content delivery network (CDN); zero-rating; throttling